FIGO good practice recommendations on magnesium sulfate administration for preterm fetal neuroprotection. Issue 1 (14th September 2021) - Shennan, Andrew; Suff, Natalie; Jacobsson, Bo
Abstract: In women at risk of early preterm imminent birth, from viability to 30 weeks of gestation, use of MgSO4 for neuroprotection of the fetus is recommended. In pregnancies below 32–34 weeks of gestation, the use of MgSO4 for neuroprotection of the fetus should be considered. MgSO4 should be administered regardless of the cause for preterm birth and the number of babies in utero. MgSO4 should be administered when early preterm birth is planned or expected within 24 h. When birth is planned, MgSO4 should commence as close as possible to 4 h before birth. If delivery is planned or expected to occur sooner than 4 h, MgSO4 should be administered, as there is still likely to be an advantage from administration within this time. The optimal regimen of MgSO4 for fetal neuroprotection is an intravenous loading dose of 4 g (administered slowly over 20–30 min), followed by a 1 g per hour maintenance dose. This regimen should continue until birth but should be stopped after 24 h if undelivered. When MgSO4 is administered, women should be monitored for clinical signs of magnesium toxicity at least every 4 h by recording pulse, blood pressure, respiratory rate, and deep tendon (for example, patellar) reflexes. Synopsis: MgSO4 for fetal neuroprotection is recommended to women at risk of imminent preterm birth below 30 weeks of gestation.